Differences Basketball Lay-up achievement elementary school upper class based on sexs - Isti Dwi Puspita Wati (PHEDHERAL, 2023)
Doing a lay-up is one of the most important basketball skills. The lay-up ability further develops the basic throwing motion applied in basketball. This ability becomes important as one of the basic techniques to generate points. The opportunity to move between sons and daughters in physical education is sometimes different. Age in the range of 9-11 years is a period of rapid growth and development which results in movement maturity. This study aimed to describe differences in the ability to do a lay-up in basketball by looking at gender as a differentiating variable. The sample consisted of 127 students, 60 boys, and 67 girls. The lay-up ability test is carried out by giving five chances. The data were analyzed with the help of Excel software and IBMSPSS series 22. The results of the non-parametric analysis showed that there were differences in the results of the lay-up between boys and girls. This is indicated by the results of the non-parametric test with a significance value of 0.00 with a mean of 2.46 for men and 1.74 for women. This study concludes that the lay-up abilities of male and female upper-class students are significantly different.